Epidemiological changes in Eisenmenger syndrome in the Nordic region in 1977–2012. Issue 17 (27th April 2017) - Hjortshøj, Cristel Sørensen; Jensen, Annette Schophuus; Sørensen, Keld; Nagy, Edit; Johansson, Bengt; Kronvall, Thomas; Dellborg, Mikael; Estensen, Mette-Elise; Holmstrøm, Henrik; Turanlahti, Maila; Thilén, Ulf; Søndergaard, Lars
Abstract : Objective: Improved diagnostic tools, timely closure of the shunt and a better understanding of the complexity of Eisenmenger syndrome (ES) have led to improved care and treatment in tertiary centres. These may have decreased the incidence of ES and improved survival of patients with ES, although evidence is still lacking. The aim of this study was to investigate temporal changes in incidence, prevalence and mortality in patients with ES for 35 years in the Nordic region. Methods: This was a retrospective population-based study including 714 patients with ES. Survival analysis was performed based on all-cause mortality and accounting for immortal time bias. Results: The incidence of ES decreased from 2.5/million inhabitants/year in 1977 to 0.2/million inhabitants/year in 2012. Correspondingly, prevalence decreased from 24.6 to 11.9/million inhabitants. The median survival was 38.4 years, with 20-year, 40-year and 60-year survival of 72.5%, 48.4%, and 21.3%, respectively. Complex lesions and Down syndrome were independently associated with worse survival (HR 2.2, p<0.001 and HR 1.8, p<0.001, respectively). Age at death increased from 27.7 years in the period from 1977 to 1992, to 46.3 years from July 2006 to 2012 (p<0.001). Conclusions: The incidence and prevalence of ES in the Nordic region have decreased markedly during the last decades. Furthermore, the median age at death increased throughout the study period, indicating prolonged life expectancy in the ES population. However, increasing age represents decreased incidence, rather than improved survival. Nonetheless, longevity with ES is still shorter than in the background population.